How the cell cycle clock ticks - Örd, Mihkel (Mol Biol Cell, 2019)
Eukaryotic cell division has been studied thoroughly and is understood in great mechanistic detail. Paradoxically, however, we lack an understanding of its core control process, in which the master regulator of the cell cycle, cyclin-dependent kinase (CDK), temporally coordinates an array of complex molecular events. The core elements of the CDK control system are conserved in eukaryotic cells, which contain multiple cyclin–CDK forms that have poorly defined and partially overlapping responsibilities in the cell cycle. However, a single CDK can drive all events of cell division in both mammalian and yeast cells, and in fission yeast a single mitotic cyclin can drive the cell cycle without major problems. But how can the same CDK induce different events when activated at different times during the cell cycle? This question, which has bewildered cell cycle researchers for decades, now has a sufficiently clear mechanistic answer. This Perspective aims to provide a synthesis of recent data to facilitate a better understanding of this central cellular control system.